How to find work for the rest of your life - Austin, Charles Michael (Chaz Austin, 2024)
Welcome to The Gig Economy! The job market of the 21st Century is radically different from the one in which our parents and grandparents lived. Corporate loyalty is largely dead. Corporations today are focused on pleasing shareholders and cutting costs. Their biggest cost? Labor. Meaning you. So you're now on your own. Your own brand. Essentially your own business. This book offers a paradigm shift in how you'll think - and act - in the working world from now on. "How to Find Work for the Rest of Your Life" will show you how to define, articulate and sell your brand to the target markets who will pay for your skill set. You will be able to apply the principles you learn here, no matter what you'll be doing, for as long as you choose to work.
Keywords: Career development -- United States; Occupational mobility; Job hunting; Vocational guidance; Plan de carrière; États-Unis; Mobilité professionnelle; Recherche d'emploi